International Breastfeeding Journal: Introducing a new journal - Amir Lisa H (BMC, 2006)
Abstract International Breastfeeding Journal is a new open access peer-reviewed journal with a multidisciplinary focus. The aim of International Breastfeeding Journal is to contribute to understanding all aspects of breastfeeding. Breastfeeding is recognized as an important public health issue with enormous social and economic implications. In order to help women breastfeed successfully there is a need to understand both the physiology of lactation and the social and cultural context within which breastfeeding occurs. International Breastfeeding Journal invites manuscripts from around the world, which address all of these aspects, including the impediments to breastfeeding, the health effects of not breastfeeding for infants and their mothers, and the management of breastfeeding problems.